2022
DOI: 10.3389/fnins.2022.1000179
|View full text |Cite
|
Sign up to set email alerts
|

MS-based glycomics: An analytical tool to assess nervous system diseases

Abstract: Neurological diseases affect millions of peopleochemistryorldwide and are continuously increasing due to the globe’s aging population. Such diseases affect the nervous system and are characterized by a progressive decline in brain function and progressive cognitive impairment, decreasing the quality of life for those with the disease as well as for their families and loved ones. The increased burden of nervous system diseases demands a deeper insight into the biomolecular mechanisms at work during disease deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 325 publications
0
8
0
Order By: Relevance
“…Table 1 and Supplemental Table 4 list all the sialylated glycoforms accumulated in Neu1 ΔEx3 kidney tissues and provide a relative quantitative comparison between WT and Neu1 ΔEx3 mice. To analyze sialic acid linkages, we also performed N-glycoprofiling by HILIC-UPLC-FLR-ESI-MS ( 37 ) capable of distinguishing between α2,3- and α2,6-linked sialic acids ( 38 ). These analyses verified major increases of oligomannose and sialylated N-glycans in Neu1 ΔEx3 mice ( Supplemental Figure 8A ) and indicated that the ratio of α2,3- to α2,6-linked sialic acids was similar in WT and in Neu1 ΔEx3 mice, as illustrated by the representative extracted ion current for the disialo-biantennary core-fucosylated structure with m/z 1,341.0150 ( Supplemental Figure 8B ).…”
Section: Resultsmentioning
confidence: 99%
“…Table 1 and Supplemental Table 4 list all the sialylated glycoforms accumulated in Neu1 ΔEx3 kidney tissues and provide a relative quantitative comparison between WT and Neu1 ΔEx3 mice. To analyze sialic acid linkages, we also performed N-glycoprofiling by HILIC-UPLC-FLR-ESI-MS ( 37 ) capable of distinguishing between α2,3- and α2,6-linked sialic acids ( 38 ). These analyses verified major increases of oligomannose and sialylated N-glycans in Neu1 ΔEx3 mice ( Supplemental Figure 8A ) and indicated that the ratio of α2,3- to α2,6-linked sialic acids was similar in WT and in Neu1 ΔEx3 mice, as illustrated by the representative extracted ion current for the disialo-biantennary core-fucosylated structure with m/z 1,341.0150 ( Supplemental Figure 8B ).…”
Section: Resultsmentioning
confidence: 99%
“…It is interesting to speculate the potential role trans ligands of CD33M could have in vivo. This is especially worth exploring in the context of AD brain, as dramatic changes have been observed in the brain glycome of animal models of AD as well as human patients [69][70][71]. Recent advances in understanding human sialome and elucidation of the glycan ligands of CD33 [72][73][74][75] could be instrumental in spatial characterization of glycan ligands of CD33M at both regional and cellular levels in the brain, their changes during the course of disease, and their potential role in modulating microglia.…”
Section: Discussionmentioning
confidence: 99%
“…Although the site of modification was not established, these two glycosylated proteoforms were significantly increased in the patients with MuSc with respect to healthy controls. Indeed, altered glycoprotein expression and glycosylation aberrations, consisting of increased glycan size, extra branching of glycan chains, over-sialylation, or over-fucosylation, were associated with many diseases, especially cancer and neurological disorders [ 165 , 166 ]. A recent magistral review [ 158 ] evidences the complexity of the relationships between enzymatic glycosylation and other factors and their molecular alterations as potential diagnostic markers in many diseases.…”
Section: Glycosylationmentioning
confidence: 99%